Allergen extracts for immunotherapy: to mix or not to mix?. Issue 3 (3rd March 2016) - Nony, Emmanuel; Martelet, Armelle; Jain, Karine; Moingeon, Philippe
ABSTRACT: Allergen immunotherapy (AIT) is established as a curative treatment for allergic rhinitis, asthma, as well as insect venom allergy. AIT is based on the administration of natural allergen extracts via the subcutaneous or sublingual routes to reorient the immune system towards tolerogenic mechanisms. In this regard, since many patients are poly-allergic, mixtures of allergen extracts are often used with a potential risk to cause allergen degradation, thereby affecting treatment efficacy. Herein, we discuss the advantages and drawbacks of mixing homologous (i.e., related) or heterogeneous (i.e., unrelated) allergen extracts. We provide evidence for incompatibilities between mixes of grass pollen and house dust mite extracts containing bodies and feces, and summarize critical points to consider when mixing allergen extracts for AIT.